Smärtlindring i samband med vaccination av fisk - Axén, Charlotte (2004)
Vaccination of fish can be assumed to cause pain. This study was designed to see if we can minimize the suffering of fish following vaccination. Fishes are cold-blooded animals and thus more primitive than warm-blooded animals. Despite this, many organs, e.g. the nervous system, have the same basic structure as that of other vertebrates. The fibre system for conducting pain is more diffuse than in humans. No specific pain conducting tract seems necessary for pain transmission. All ethical rules and laws for animals include fish, but pain killing is still not common in fish production.